Cs2Zr1−xTexCl6 Perovskite Microcrystals with Ultrahigh Photoluminescence Quantum Efficiency of 79.46% for High Light Efficiency White Light Emitting Diodes. Issue 19 (25th June 2021) - Li, Zhilin; Rao, Zhihui; Li, Qiaoqiao; Zhou, Liujiang; Zhao, Xiujian; Gong, Xiao
Abstract: Recently, lead‐free materials with stable photoluminescence (PL) at room temperature, such as vacancy‐ordered double perovskites have drawn wide attention. Herein, Te 4+ ‐doped all‐inorganic lead‐free Cs2 Zr1− x Te x Cl6 perovskite microcrystals (MCs) are reported. The obtained pure Cs2 ZrCl6 perovskite MCs exhibit a blue emission, while Cs2 Zr1− x Te x Cl6 perovskite MCs show a broad and strong yellow emission with ultrahigh photoluminescence quantum yield (PLQY) up to 79.46% at room temperature. The structure and optical properties of perovskite MCs are investigated in detail by experiments and theoretical calculations. The mechanism that 3 P1 of Te can be partially frozen at the low temperature regarding Cs2 Zr1− x Te x Cl6 perovskite MCs is proposed. White light emitting diodes (WLEDs) with a color coordinate of (0.344, 0.333), a correlated color temperature of 4959 K, a color rendering index (Ra) of 74.8, and a high light efficiency of 91.16 lm W −1, are fabricated by the prepared Cs2 Zr1− x Te x Cl6 perovskite MCs powder with a commercial near‐UV LED (NUV‐LED) chip (450 nm). The results suggest that Te 4+ ‐doped all‐inorganic lead‐free perovskite MCs show great potential in the next‐generation solid‐state lightings. Abstract : Te 4+ ‐doped all‐inorganic lead‐free Cs2 Zr1− x Te x Cl6 perovskite microcrystals (MCs) can be prepared, which show a broad and strong yellow emission with ultrahigh photoluminescence quantum yield up to 79.46% at room temperature. It is interesting that 3 P1 of Te can be partially frozen at the low temperature regarding Cs2 Zr1− x Te x Cl6 perovskite MCs.